The Effect Of Cloud And Inbound Marketing On Purchase Decisions For Gold Savings - Muh. Shadri Kahar Muang; Muzayyanah Jabani; Rikal Fajar Masati (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2022)
This study aims to show the effect of cloud and inbound marketing on purchase decisions for gold savings at Bank Syariah Indonesia (BSI). This study uses a quantitative approach. The population in this study was 1286 people with a sample of 305 people. Data were collected using a questionnaire. Data were analyzed using multiple linear regressions. This study indicates that cloud marketing does not affect purchase decisions for gold savings. However, inbound marketing significantly influences purchase decisions for gold savings. Cloud and inbound marketing simultaneously significantly influence purchase decisions for gold savings with a contribution of 57.4%, and other factors influence the rest. This study complements a new perspective on marketing in industry 4.0. Practically it can be used as a reference for BSI management in making marketing decisions to embrace customers to save gold. This study can be used as a reference for developing marketing strategies for Islamic banking products in the future. Islamic banking practitioners can adopt practically cloud and inbound marketing as a strategy to reach customer purchasing decisions.